A PENGARUH PEMBELAJARAN LESSON STUDY BERBASIS PROYEK DALAM BENTUK INFOGRAFIS DAN KETERAMPILAN 4C TERHADAP HASIL BELAJAR METODOLOGI PENELITIAN DENGAN KOVARIABEL MOTIVASI MAHASISWA : Hasil Belajar, Infografis, Keterampilan 4C, Motivasi, PjBL - Yulianto, Dwi (Mathematics Education Study Program, FKIP, Universitas Pasundan, 2023)
The lessons that can be used to solve teacher problems in this pandemic era is Lesson Study (LS) learning which can be projects Infoghrafic presentations and 4C (Critical Thinking and Problem Solving, Creativity and Innovation, Communication, dan Collaboration) thinking skills on research methodology. The purpose of this study is to further project-based LS learning is infoghrafic form in order to increase students' motivation and 4C thinking skills. This research uses Lesson Study has: preparing, performing, reflecting (checking) and follow up (act). The research design used was quasi-experiment, single factor independent groups design with use of covariate. The subject of this study was students of STKIP La Tansa Mashiro with the sample used totaling 46 students and technique used purposive sampling. The data in this study were using the Non-test and test. Data were analyzed test using the Anava One Way, Anacova and Product moment. The results, that: 1) there was LS learning which of projects through Infoghrafic presentations on 4C learning on reaserch of methodology. 2) There was the effect LS learning which of projects through Infoghrafic presentations on 4C learning on reaserch of methodology with students motivation covariable. 3) There was a significant effect between students motivation and reaserch of methodology. The results that LS learning which of projects through Infoghrafic presentations on 4C learning on reaserch of methodology and there is contribution students motivation towards learning outcomes in on methodology.